Optical control of polarization in ferroelectric heterostructures - Tao Li (Nature Portfolio, 2018)
Controlling the polarization state in ferroeletric materials is a prerequisite for their application. Here an approach is presented to optically manipulate the polarization of ferroelectric BaTiO3 by exploiting photogenerated carriers at the interface with a two-dimensional semiconducting MoS2 film.